PENGARUH CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) 2010-2012 - Raja Aldino; Yusralaini Yusralaini; Sem Paulus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims are to provide empirical evidence of the influence of institutional ownership, managerial ownership, the proportion of independent board of commissioners, and audit quality toward the corporate value of manufacturing companies in Indonesia Stock Exchange.The population in this study are all companies listed in Indonesia Stock Exchange (IDX). Sampling was done using purposive sampling method that determinated the sample with a specific target or consideration. Based on data collection there are 79 manufacturing companies listed in Indonesia StockExchange can be used as a sample. To analyse the data is using multiple regression method.The study states that the audit quality does not have a significant effect on company value, independent commissioner does not have a significant effect on company value, institutional ownership has no significant effect on companyvalue. While managerial ownership has a significant impact on corporate value. This means that managerial ownership is a factor that needs to be used as a material consideration in the management of the company.Keywords : Audit Quality, Independent Commissioner, Institutional Ownership, Managerial Ownership, Company Value .